Algebraic Structure and Poisson Integral Method of Snake-Like Robot Systems - Jing-Li, Fu; Chun, Xiang; Lei, Meng (Frontiers in Physics, 2021)
The algebraic structure and Poisson’s integral of snake-like robot systems are studied. The generalized momentum, Hamiltonian function, generalized Hamilton canonical equations and their contravariant algebraic forms are obtained for snake-like robot systems. The Lie-admissible algebra structures of the snake-like robot systems are proved and partial Poisson integral methods are applied to the snake-like robot systems. The first integral methods of the snake-like robot systems are given. An example is given to illustrate the results.